Tingkat Kepatuhan Pejabat Pengadaan Pada Peraturan Pengadaan Barang Dan Jasa Terhadap Kegiatan Pengadaan Barang Publik Di Provinsi Papua Barat - Maturbongs, Leonardus; Supriyantono, Andoyo; A. Baransano, Michael (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: Government Procurement of Goods and Services is an activity to obtain Goods and Services by the Regional Apparatus Work Unit, Institutions, Ministries, and other institutions whose process begins with planning needs to complete activities to obtain Goods and Services. The Procurement of Goods and Services activities are also carried out in West Papua Province, one of which is the Public Goods Procurement Activity. From the Public Procurement activities, it is hoped that it can run by the Rules for Procurement of Goods and Services. This is of course a concern for all those involved in the Procurement of Goods and Services Activities and one of them is the Government in this case the Goods and Services Procurement Officer at the Regional Apparatus Organization in West Papua Province. The purpose of this writing is to determine the Level of Compliance of Procurement Officials in the Procurement regulations on Goods and Services to Public Procurement activities in West Papua Province. This research was conducted using analytical descriptive methods. The research was conducted by interviewing and collecting data using questionnaires to the Goods and Services Procurement Officers at the Regional Apparatus Organization in West Papua Province. The sample technique or sampling technique in this study used Simple Random Sampling. To determine the Level of Compliance of Procurement of Goods and Services, the data was processed using a Likert scale which is determined by the score and then the results are analyzed descriptively. The results showed that the Level of Compliance of Procurement Officials in the Procurement regulations on Goods and Services to Public Procurement activities in West Papua Province was High.